(untitled) (Journal of Advances and Scholarly Researches in Allied Education, 2021)
The hypothesis can be stated as “Impact of Employee Empowerment on Job Satisfaction in Banking Sector with reference to Chennai city”. Both primary and secondary data were used for this research. Primary data was collected to assess the level of empowerment and the level of job satisfaction of the respondents. Secondary data was collected from various sources. On the beginning, to gain knowledge about the banking industry secondary data was used. The secondary sources of data include reports, books, manuals, newspapers, journals and published and unpublished sources and bank employees associations etc. The method used for primary data collection is through questionnaires. To assess the level of employee empowerment questions have chosen from different authors. Similarly to assess the level of job satisfaction a standardized instrument namely the MSQ - Minnesota Satisfaction Questionnaire developed by Weiss et al in 1967 was used. The population of the study was more than 7825 in number and with this population a pilot study was conducted on a sample of 50 respondents in order to arrive at the appropriate sample size for the research. Hence sample size was derived using the formula as 513.